AESTHETICS AND RECEPTION OF THE QUR’AN IN THE CALLIGRAPHY OF MOSQUES IN PROBOLINGGO INDONESIA - Fawaid, Ahmad; Sultoni, Ahmad Bakir (Universitas Nurul Jadid, 2022)
The art of calligraphy, the greatness of Islamic art, was naturally born amid the world of architecture. This can be proven in the various calligraphic decorations that fill mosques and other buildings, combined with the noble Qur’anic verses, hadiths, or the wise words of wise scholars. The Qur’an is written in various models of calligraphy with dazzling and varied decorations. This study analyzes the Aesthetics and Calligraphy Reception of the Probolinggo Regency Mosque from the perspective of the Living Qur’an. With the living Qur’an method, God’s verbal revelation is expressed in a tangible form in writing, which has been a long debate and has influenced civilization. The Qur’an became the main factor in the development of the art of Islamic calligraphy, so calligraphy was expressed to devote the power of the revelation of the Qur’an. Meanwhile, ornamentation is the development of a sense of beauty that is free from natural myths and is done by developing abstract patterns taken from the processing of floral, leaf, and polygon motifs. This study concludes that the aesthetics and reception of calligraphy at the Probolinggo mosque can be considered uniform, both at the Badridduja, Ar Raudhah, and Raudhatul Jannah mosques, even though the texts chosen are not the same. The color choices converge on green and gold, indicating they are identical to Islam, where the symbolic meanings are plants, trees, leaves, and forests. Meanwhile, the psychological meaning of green is growth, renewal, balance, harmony, and the environment. Green color mixed with Gold color, the eyes that will look at it make you feel happy with all the artful writing.